THE EFFECT OF COMPENSATION, WORK LIFE BALANCE, AND WORK ENVIRONMENT ON EMPLOYEE WORK LOYALTY IN TELECOMMUNICATIONCOMPANIES IN BANDAR LAMPUNG - Feditya Irsya Alpanda; Defia Riski Anggarini; Almira Devita Putri (Universitas Teknokrat Indonesia, 2023)
The Covid-19 pandemic has had an impact on the business sector in Indonesia. The business sector also has an impact on telecommunications companies in Bandar Lampung which are engaged in telephone and short message services as well as internet services. This pandemic also has an impact on employees of telecommunications companies in Bandar Lampung. The impact felt by the employees themselves, such as in terms of providing compensation, regulating work life balance, and managing the work environment. This study aims to determine the effect of compensation, work life balance, and work environment simultaneously and partially on employee work loyalty at a telecommunications company in Bandar Lampung. This study uses quantitative methods with a sample of 200 respondents. Based on the test results simultaneously or partially, it is found that there is an influence that compensation, work life balance, and work environment partially affect employee work loyalty. The three variables proved to be partially influential because the value of t count > t table and significance value < 0.05. The results of this study also show that compensation, work life balance, and work environment simultaneously affect employee work loyalty because the value of f count > f table with a significance value of < 0.05.Keywords: Compensation, Work Life Balance, Work Environment, Employee Loyalty.